Does access to microfinance matter for rural women? - Neupane, Hari Sharma; Paudel, Krishna Prasad (Technical Centre for Agricultural and Rural Cooperation, 2018)
Due to the unavailability of financial services, the lack of products, and the cost of credit, many low-income households struggle to manage their savings and invest in, and expand, small businesses. Women, as well as poor and deprived groups, are unable to manage inputs and technologies to make their farms more productive. To boost local entrepreneurship, the Improved Seeds for Farmers’ Programme (KUBK-ISFP) set out to establish 30 financial institutions to increase women’s financial inclusion. Membership of a microfinance cooperative has been found to improve women’s empowerment and the livelihoods of poor farmers.